2001
DOI: 10.1097/00042728-200102000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Facial Rejuvenation with a Nonablative 1320 nm Nd:YAG Laser

Abstract: background. Rejuvenation of photoaged skin involves removal of the epidermis and superficial dermis, encouraging the production of new epidermis with collagenesis and remodeling. The facial appearance during healing is unpleasant, and the complication rate is high. objective. We evaluate a Q-switched Nd:YAG laser operating at 1320 nm, with a cryogen delivery system and a skin temperature sensor. The system cools the target skin, followed by the laser impulse which passes through the cooled epidermis into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 10 publications
4
73
0
1
Order By: Relevance
“…11,15-17 Trelles et al 17 reported disappointing results after treating 10 patients with a 1320-nm Nd:YAG laser in a series of 8 treatments over a 4-week period, with only 2 of 10 patients expressing satisfaction with the results of their treatment. However, Trelles 18 followed up with a letter to the editor indicating that unpublished long-term data showed better results than the preliminary study, and that 4 weeks was not sufficient time to draw conclusions about the efficacy of the treatments.…”
Section: Commentmentioning
confidence: 99%
“…11,15-17 Trelles et al 17 reported disappointing results after treating 10 patients with a 1320-nm Nd:YAG laser in a series of 8 treatments over a 4-week period, with only 2 of 10 patients expressing satisfaction with the results of their treatment. However, Trelles 18 followed up with a letter to the editor indicating that unpublished long-term data showed better results than the preliminary study, and that 4 weeks was not sufficient time to draw conclusions about the efficacy of the treatments.…”
Section: Commentmentioning
confidence: 99%
“…Although non-ablative laser treatment has delivered increased clinical safety, this has often come at a cost of predictable and consistent efficacy [9,10]. More recently, a major advance in non-ablative laser treatment, termed fractional photothermolysis, was reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…Later Goldberg performed a series of clinical studies with histologic examinations to prove the collagen remodeling effects of Q-switched 1,064-nm Nd:YAG laser [2,3]. The 1,320-nm Nd:YAG laser with a dynamic surface cooling device was the first laser system specifically designed for the purpose of non-ablative skin rejuvenation [4][5][6]. Trelles et al [5] investigated the histological changes in human skin 6 weeks after 8 treatments with the 1,320-nm Nd:YAG laser and observed that there is an increase in the number and density of collagen fibers, indicating some compaction in the remodeling process, less interfibrillary space, and good linear orientation of the fibers parallel to the dermoepidermal junction.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,320-nm Nd:YAG laser with a dynamic surface cooling device was the first laser system specifically designed for the purpose of non-ablative skin rejuvenation [4][5][6]. Trelles et al [5] investigated the histological changes in human skin 6 weeks after 8 treatments with the 1,320-nm Nd:YAG laser and observed that there is an increase in the number and density of collagen fibers, indicating some compaction in the remodeling process, less interfibrillary space, and good linear orientation of the fibers parallel to the dermoepidermal junction. The pulsed dye laser (PDL) is commonly used to treat port wine stains, hemangiomas, telangiectasias, and other vascular anomalies [7,8].…”
Section: Introductionmentioning
confidence: 99%